A systematic review of prerequisites for implementing assessment for learning in classroom practice - Heitink, M.C.; Van der Kleij, F.M.; Veldkamp, B.P.; Schildkamp, K.; Kippers, W.B. (Educational research review, 2016)
Although many researchers acknowledge that Assessment for Learning can significantly enhance student learning, the factors facilitating or hindering its implementation in daily classroom practice are unclear. A systematic literature review was conducted to reveal prerequisites needed for Assessment for Learning implementation. Results identified prerequisites regarding the teacher, student, assessment and context. For example, teachers must be able to interpret assessment information on the spot, student engagement in the assessment process is vital, assessment should include substantial, constructive and focussed feedback, and the school should have a school-wide culture that facilitates collaboration and encourages teacher autonomy. The results of this review contribute to a better understanding of the multiple facets that need to be considered when implementing Assessment for Learning, from both a theoretical and a practical standpoint. •Identified various prerequisites for Assessment for Learning in the classroom.•Teachers and students require certain knowledge, skills and attitudes.•Results highlight importance of leadership, culture and professional development.•There is limited evidence on prerequisites for students in AfL.•Presents a conceptual model of prerequisites for AfL implementation.